Secure-Rpl: Approach To Prevent Resource-Based Attacks In Wireless Sensor Networks Using Balanced Clustering - Alhamead Al Absi, Basim Ahmad Abed (2020)
Internet of Things (IoT) is an evolving computing technology that enables an interconnection amongst physical devices, which offers many advantages, such as easy access to information, cost effectiveness, automation, efficient resource utilisation, reduced human effort and high productivity, all of which have attracted many industry players and researchers. However, the involvement of a vast number of devices and IoT users introduces many issues, including those related to quality of service and security. In IoT, routing amongst resource-constrained devices and nodes is realised by using the routing protocol for a low-power and lossy network (RPL), which selects an optimal route according to the specific objective function.